Internal phosphate starvation signaling and external phosphate availability have no obvious effect on the accumulation of cadmium in rice - Xue-qing WANG; Wen-yuan RUAN; Ke-ke YI (Journal of Integrative Agriculture, 2019)
Phosphorus (P) is a limiting nutrient element for crop. To obtain maximum crop yield, P fertilizer is often over-applied, which leads to accelerating exhaustion of phosphate resources and serious environmental problems. Reducing the application of P fertilizer and enhancing the P utilization efficiency of crops are significant for the sustainable development of agriculture. Cadmium (Cd) contamination in rice is another serious agricultural issue. However, whether reducing the application of P fertilizer and enhancing the P utilization efficiency of crops will increase the risk of Cd accumulation in crops remains obscure. In this study, we are aiming to elucidate the relationship between Cd and P in rice from physiological and genetic perspectives. For this purpose, the wild type (WT) rice plants and phosphate (Pi)-starvation signaling repressed mutant phr2 were used to analyze the relationship between Cd and P. Here, we found that Cd stress could promote P accumulation and induce Pi-starvation signaling in WT and phr2 shoots under Pi-sufficient condition in a PHOSPHATE STARVATION RESPONSE 2 (PHR2) independent manner. Besides, the expression level of Cd transporter of OsNramp5 and the uptake speed of Cd2+ were not obviously changed under Pi-sufficient and Pi-deficient conditions. Furthermore, our Cd determination results showed that the Cd concentrations in WT and phr2 were not obviously changed under Pi-sufficient and Pi-deficient conditions. These results indicate that the external P availability and internal Pi-starvation signaling cannot obviously affect the accumulation of Cd in rice seedling.